Pengaruh Sertifikasi Guru dan Motivasi Terhadap Kinerja Guru di SMA Negeri Sekecamatan Kayuagung - Eva Susanti; Tri Widayatsih; Mulyadi Mulyadi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the effect of certification and motivation on teacher performance. The location of this research was carried out at public high schools in the Kayuagung District. This type of research is quantitative research with a research design using an ex post facto research design. The sample in this study was a total of all teachers in public high schools in the Kayuagung District, consisting of 122 teachers. data collection technique using a questionnaire. Data analysis techniques using descriptive quantitative analysis techniques, and multiple regression. The results of this study state that 1) there is a significant influence between school teacher certification on the performance of public high school teachers in the Kayuagung District; 2) there is a significant influence between motivation on the performance of State Senior High School teachers in the Kayuagung District; 3) there is a significant effect of teacher certification and motivation together on the performance of teachers in public high schools in the Kayuagung District. These results suggest that the higher the qualification of a certified teacher, the higher the performance. Then, motivation within the teacher will have an impact on teacher performance.